2015
DOI: 10.1371/journal.pone.0119336
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Expression Profile and Involvement of Let-7d-APP in Aged Rats with Isoflurane-Induced Learning and Memory Impairment

Abstract: MicroRNAs (miRNAs) play a key role in different nervous system diseases. We sought to determine the role of miRNAs in isoflurane-induced learning and memory impairment in aged rats. Male Sprague-Dawley (SD) rats of 18 month were randomly assigned to control group (exposed to mock anesthesia), 2-hour group and 6-hour group (exposed to 2% isoflurane for 2 and 6 hours respectively). By Morris Water Maze, 6-hour group showed impaired learning and memory ability while 2-hour group not. As shown by miRNA array, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Let-7d is abundant in the brain. In fact, using a microarray screening, Shu and colleagues found that let-7d was up-regulated in the hippocampus and the Marginal division (MrD) of the neostriatum ( Shu et al, 2013 ), suggesting that it may play an important role in modulating learning and memory ( Luo et al, 2015 ). Also, let-7d, which is increased in the prefrontal cortex of spontaneously hypertensive rats' brain, negatively regulated galectin-3 which was associated with attention deficit hyperactivity disorder development ( Wu et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Let-7d is abundant in the brain. In fact, using a microarray screening, Shu and colleagues found that let-7d was up-regulated in the hippocampus and the Marginal division (MrD) of the neostriatum ( Shu et al, 2013 ), suggesting that it may play an important role in modulating learning and memory ( Luo et al, 2015 ). Also, let-7d, which is increased in the prefrontal cortex of spontaneously hypertensive rats' brain, negatively regulated galectin-3 which was associated with attention deficit hyperactivity disorder development ( Wu et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia-induced cognitive impairment is a recognized clinical phenomenon and possibly the most frequent type of postoperative cognitive impairment ( 3 , 4 ). miRNAs had been reported to be associated with cognitive ability ( 34 , 35 ). The present study aimed to investigate the effect of miR-383 expression on propofol-induced learning and memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, AGO2 immunoprecipitation (AGO2-IP) assays were used to demonstrate that the sponges were enriched in the AGO2-IP fraction [39]. Given that miRNAs have been implicated not only in cancer but in numerous neurological [42]- [44], cardiovascular [45]- [47] and autoimmune diseases [48]- [50], the miRNA sponges could be another useful tool in the arsenal for combatting disease.…”
Section: Health Relevance and Potential Uses In Biomedicinementioning
confidence: 99%